Effect of Recycled Rubber on the Properties of Road Bitumen - Krzysztof Blażejowski; Barbara Gawdzik; Tadeusz Matynia (Journal of Chemistry)
Commercially available road bitumen 50/70 (EN 12591) was modified by recycled rubber and synthetic poly(butadiene) in the presence of sulfur donor. Modification was carried out at 190°C and 220°C. Under such conditions, devulcanization of rubber took place. Prolonged heating in the presence of sulfur caused that devulcanized rubber and poly(butadiene) to revulcanize. The influence of rubber concentration as well as temperature and time of the modification process on the properties of resulted bitumens was studied. The results show that proposed process modifies the properties of base bitumen very effectively. Particularly noteworthy are values of Fraass breaking points, melting temperatures, penetrations, and elastic recoveries.